2015
DOI: 10.1103/physreva.91.032702
|View full text |Cite
|
Sign up to set email alerts
|

Proton-hydrogen collisions at low temperatures

Abstract: We study the proton-hydrogen collision in the energy range from 0 to 5 K where the hyperfine structure of the hydrogen atom becomes important. A proper multichannel treatment of the hyperfine structure is found to be crucial at cold temperatures compared to the elastic approximation traditionally used at higher temperatures. Both elastic and hyperfine-changing inelastic processes are investigated, using both the multichannel quantum-defect theory (MQDT) and the coupled-channel numerical method. Results from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While some computational studies did observe the k −1 scaling [16,21,39] others reported that the ICS for atomic EE collisions approach a constant value [35,38,40,41], a highly unexpected observation that has, to our knowledge, remained unexplained. Several authors attributed the k 0 scaling to a deficiency of the elastic approximation [55][56][57], which effectively neglects the hyperfine structure of colliding atoms [19,38,39]. More recently, the constant near-threshold scaling of spin-exchange cross sections was claimed to be incorrect [39], further deepening the existing controversy surrounding the threshold behavior of EE collisions.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…While some computational studies did observe the k −1 scaling [16,21,39] others reported that the ICS for atomic EE collisions approach a constant value [35,38,40,41], a highly unexpected observation that has, to our knowledge, remained unexplained. Several authors attributed the k 0 scaling to a deficiency of the elastic approximation [55][56][57], which effectively neglects the hyperfine structure of colliding atoms [19,38,39]. More recently, the constant near-threshold scaling of spin-exchange cross sections was claimed to be incorrect [39], further deepening the existing controversy surrounding the threshold behavior of EE collisions.…”
mentioning
confidence: 75%
“…It is commonly believed that the inelastic ICSs scale as k −1 with the incident collision wavevector k in the limit k → 0 [53,54]. While some computational studies did observe the k −1 scaling [16,21,39] others reported that the ICS for atomic EE collisions approach a constant value [35,38,40,41], a highly unexpected observation that has, to our knowledge, remained unexplained. Several authors attributed the k 0 scaling to a deficiency of the elastic approximation [55][56][57], which effectively neglects the hyperfine structure of colliding atoms [19,38,39].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Specifically, we expect, to the lowest order, approximately one parameter per potential energy curve (PEC) and a few parameters per potential energy surface (PES), with allowance for a few more coupling constants if there are multiple curves and/or surfaces that cross or interact strongly in the short range. For atom-atom interactions, this efficient parameterization is accomplished through a frame transformation [34,57], and has been fully demonstrated for alkali-alkali interactions in the context of isotropic MQDT [29,34,43,[115][116][117][118][119][120][121]. In MQDTA, the more general frame transformations of Ref.…”
Section: E Short-range Parametersmentioning
confidence: 99%